Production and stability study of a hospital parenteral nutrition solution for neonates - Anne-Laure Yailian; Céline Serre; Justine Fayard; Marina Faucon; Patrick Thomaré; Samira Filali; Christine Pivot; Florence Vételé; Fabrice Pirot; Emmanuelle Olivier (Elsevier, 2019)
Standard parenteral nutrition solutions are mixtures comprising interacting components that may degrade themselves over time. The objective of this study was to investigate the physicochemical and microbiological stability of a hospital preparation for parenteral nutrition in neonatology. The analyses were performed throughout the storage of the preparations at 2-8 °C (up to 4 months). The extent of stability was based on the determination of amino acids dosage, visual and physicochemical properties (glucose and electrolytes concentrations, pH and osmolality measurements, particle counting) and microbiological analysis (sterility test). A thermal degradation of ascorbic acid was conducted to evaluate the antioxidant properties of the parenteral mixture. Physicochemical and microbiological controls were found to comply with the specifications. Amino acids showed a good stability throughout the 4months storage except for cysteine, which was progressively degraded to cystine, conferring a yellow coloration to parenteral solutions. Parenteral nutrition standards solutions remain stable for 4 months at 2-8 °C, ensuring safe administration in preterm infants. Keywords: Stability-indicating method study, Parenteral nutrition, Neonatology, Amino acids, High-performance liquid chromatographic